Drug Abuse Among Nigerian Youth and Its Consequences – A Review of Literature - Adepeju Akinlawon Adetiloye , Osunwoye Adedapo Abel* (Sokoto Journal of Medical Laboratory Science)
The available evidences suggest that it is true that drugs are used for beneficial therapeutic purposes, effective substance for good health, but they are also being abused by people especially youths. They use it illegally and unlawfully, thus it becomes harmful to the body. Studies have described a growing impact of drug abuse among Nigerian youths to the extent of being considered a moral decadent. The Nigerian youths are deliberately using drugs illegally, unlawfully and intentionally. while many are ignorantly or knowingly depending on one drug or the other for their daily activities. The objective of this review is to highlight the dangers and consequences of drug abuse particularly among the Nigerian youths. The review, which consists of literature search of journals and chapters in books, provides an insight into common drugs and substances that are abused, causes of drug abuse, social effect, prevention or control measures and laboratory investigations. Hence, for its public health significance, there is an urgent call for increased vigilance and improved knowledge/research-driven approaches to the diagnosis and management of drugs and substance of abuse.